Avaliação da toxicidade de nanopartículas de ferro na valência zero no solo: aplicação em escala de campo - Vanzetto, Guilherme Victor (2022)
The application of iron nanoparticles in zero valence is one of the most used remediation technologies today, however, the potential environmental risks of the application are largely unknown. In this sense, a bibliometric research was carried out presenting the temporal distribution of publications, most cited articles, the authors, institutions, countries and scientific journals that publish the most on the subject. Furthermore, the colony-forming units of pseudomonads and bacillus exposed to zero-valent iron nanoparticles were evaluated in a residual basalt soil after nanoremediation of a site contaminated with hexavalent chromium and pentachlorophenol on a field scale. And, the efficiency of injecting nZVI from an in situ site contaminated with hexavalent chromium and pentachlorophenol was evaluated. Bibliometrics made it possible to view an overview of publications, allowing research to be directed towards an effective contribution to science. The evaluation of pseudomonas and bacillus colony-forming units expressed the toxic potential of the substances in the soil. The process of injecting nanoiron suspensions into test specimens with organic and inorganic contaminants proved to be complex, requiring the development and assembly of equipment for applying the jet grouting technique with nanoiron suspensions on a field scale, simulating contamination in a non- saturated; Soil remediation with nZVI injection showed more than 90% efficiency in the degradation of Cr6+ and PCP contaminants. The degradation of Cr6+ was fast and constant, the contaminant PCP was more persistent in the environment, showing greater degradation after 30 days. We observed the migration of both contaminants and also of nZVI to deeper layers of the soil, however no contaminants were found in the leachate. We evaluated the toxic effect on the growth of colony forming units (CFUs) of Bacillus cereus and Pseudomona aeruginosa, temporary fluctuations in the abundance of the microbiological community were observed, characterizing the adaptation of bacteria to contaminants. The bacteria showed similar behavior, ninety days after nZVI injection the mean CFUs were statistically equal, with the lowest coefficient of variation and the highest concentration of CFUs. The B. cereus and P. aeruginosa strains were resistant to concentrations of nZVI, Cr6+ and PCP. The nanoremediation of nZVI in soil contaminated by Cr6+ and PCP did not have a toxic effect on the population of native soil bacteria and did not present major disturbances in temperature, electrical conductivity, pH and humidity over time.